Anatomy of a Small Failure - Sandra Rhoades (Journal of Research in Rural Education, 1993)
This storyhas twoparts. The firstsketches the1991 workshop I designed andled for middle-school teachersin rural Georgia. A telecommunication effort was to be an integral part of thefollow-up to theworkshop-a way to keep participants conversing and thereby decrease their isolation. It failed. In thesecond part, I detail the conditions necessary for success.